Pengaruh Pengetahuan Konsumsi Islam dan Gaya Hidup terhadap Perilaku Konsumtif Mahasiswa - Monalisa, Siska; Mutia, Agustina (Lembaga Yasin AlSys, 2025)
Consumptive behavior among university students has become an increasingly prominent phenomenon, influenced by modern lifestyles and the ease of access to consumer goods. This phenomenon is particularly worth examining among students of the Faculty of Islamic Economics and Business (FEBI) at UIN Sulthan Thaha Saifuddin Jambi, who possess an educational background in Islamic economics. This study aims to analyze the influence of Islamic consumption knowledge and lifestyle on students' consumptive behavior. A quantitative approach was employed using a survey method, with questionnaires distributed to 96 proportionally selected respondents. Data collection was conducted using a Likert-scale questionnaire, and data were analyzed through multiple linear regression to test both the partial and simultaneous effects of the independent variables on the dependent variable. The results show that both Islamic consumption knowledge and lifestyle have a positive and significant effect on consumptive behavior, both partially (significance value < 0.05) and simultaneously, as evidenced by an F-value of 57.353, which exceeds the F-table value. The Adjusted R² value of 0.543 indicates that 54.3% of the variation in consumptive behavior can be explained by the two variables. The study concludes that the greater the students’ understanding of Islamic consumption principles and the stronger the influence of modern lifestyle, the higher their tendency to exhibit consumptive behavior.